Editorial: How large is the world of global constitutionalism? - Mattias Kumm; Anthony F. Lang; James Tully; Antje Wiener (Global Constitutionalism, 2014)
As Global Constitutionalism enters its third year, we want to take the opportunity to refl ect on and explore the conceptual and institutional boundaries of the world of global constitutionalism. In our fi rst editorial two years ago we defi ned the mission of the journal to promote a deeper understanding of the foundations, limitations and principles of political order and their dynamics over time across or between states, institutions or political communities. We insisted that Constitutionalism is not to be understood primarily as the study and interpretation of a constitutive legal document, but as a reference frame for interdisciplinary research with a particular focus. We elaborated on the challenges of interdisciplinarity in our second editorial. In this year's editorial we want to refl ect further on the particular focus that comes with a constitutionalist frame of reference.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation).
Keywords: 330